Prevalence of anti-malarial resistance genes in Dakar, Senegal from 2013 to 2014. (December 2016) - Boussaroque, Agathe; Fall, Bécaye; Madamet, Marylin; Wade, Khalifa; Fall, Mansour; Nakoulima, Aminata; Fall, Khadidiatou; Dionne, Pierre; Benoit, Nicolas; Diatta, Bakary; Diemé, Yaya; Wade, Boubacar; et al.
Abstract Background To determine the impact of the introduction of artemisinin-based combination therapy (ACT) on parasite susceptibility, a molecular surveillance for antimalarial drug resistance was conducted on local isolates from the Hôpital Principal de Dakar between November 2013 and January 2014 and between August 2014 and December 2014. Methods The prevalence of genetic polymorphisms in antimalarial resistance genes (pfcrt, pfmdr1, pfdhfr andpfdhps ) was evaluated in 103 isolates. Results The chloroquine-resistant haplotypes CVIET and CVMET were identified in 31.4 and 3.9 % of the isolates, respectively. The frequency of thepfcrt K76T mutation was increased from 29.3 % in 2013–2014 to 43.2 % in 2014. Thepfmdr1 N86Y and Y184F mutations were identified in 6.1 and 53.5 % of the isolates, respectively. Thepfdhfr triple mutant (S108N, N51I and C59R) was detected in the majority of the isolates (82.3 %). The prevalence of quadruple mutants (pfdhfr S108N, N51I, C59R andpfdhps A437G) was 40.4 %. One isolate (1.1 %) harboured thepfdhps mutations A437G and K540E and thepfdhfr mutations S108N, N51I and C59R. Conclusions Despite a decline in the prevalence of chloroquine resistance due to the official withdrawal of the drug and to the introduction of ACT, the spread of resistance to chloroquine has continued. Furthermore, susceptibility to amodiaquine may be decreased as a result of cross-resistance. The frequency of thepfmdr1 mutation N86Y declined while the Y184F mutation increased in prevalence, suggesting that selective pressure is acting onpfmdr1, leading to a high prevalence of mutations in these isolates and the lack of specific mutations. The 50.5 % prevalence of thepfmdr1 polymorphisms N86Y and Y184F suggests a decrease in lumefantrine susceptibility. Based on these results, intensive surveillance of ACT partner drugs must be conducted regularly in Senegal.